2018
DOI: 10.1136/bmjopen-2017-019412
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase access to or uptake of physical health screening in people with severe mental illness: a realist review

Abstract: ObjectivesTo identify and evaluate interventions aimed at increasing uptake of, or access to, physical health screening by adults with severe mental illness; to examine why interventions might work.DesignRealist review.SettingPrimary, secondary and tertiary care.ResultsA systematic search identified 1448 studies, of which 22 met the inclusion criteria. Studies were from Australia (n=3), Canada (n=1), Hong Kong (n=1), UK (n=11) and USA (n=6). The studies focused on breast cancer screening, infection preventive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…The mechanisms identified in this review resonate with those described in two realist reviews exploring screening or referral by practitioners in other health care contexts . In O'Campo et al's review of intimate partner violence screening across a range of health care settings, they also found that most studies were multicomponent.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…The mechanisms identified in this review resonate with those described in two realist reviews exploring screening or referral by practitioners in other health care contexts . In O'Campo et al's review of intimate partner violence screening across a range of health care settings, they also found that most studies were multicomponent.…”
Section: Discussionsupporting
confidence: 59%
“…In the realist review of physical health screening in people with mental health conditions by Lamontagne‐Godwin and colleagues, interventions were divided into those focusing on health service delivery changes (eg, staff training and protocol development) and those using tools designed to facilitate screening (eg, electronic prompts). As with the O'Campo study, the authors did not employ the CMO heuristic or make any attempt to discern mechanisms or theories of change underpinning the identified intervention strategies.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations